Handbook on sport and migration / edited by Joseph Maguire, Katie Liston, Mark Falcous. - Maguire, Joseph A., 1956-; Liston, Katie; Falcous, Mark, 1973- (Edward Elgar Publishing, 2024)
Explores how sport intersects the experiences of asylum seekers, refugees, workers and migrants. Editors Joseph Maguire, Katie Liston and Mark Falcous bring together esteemed experts to capture the complex dynamics surrounding how sport migrations are embedded in the wider power struggles that characterize global sport.